Self-Assembled DNA Nanospheres: Design and Applications - Li, Jing; Liu, Xiaojun; Wang, Jiaoli; Jiang, Qi; Chen, Minhui; Zhang, Wei; Chen, Yu; Pu, Ying; Huang, Jin (Chemistry an international journal, 2023)
Self-assembled DNA nanospheres, as versatile and ideal vehicles, have offered new opportunities to create intelligent delivery systems for precise bioimaging and cancer therapy, due to their good biostability and cell permeability, large loading capacity, and programmable self–assembly behaviors. DNA nanospheres can be synthesized by the self–assembly of Y–shaped DNA monomers, ultra–long single-stranded DNA (ssDNA), and even metal–DNA coordination. Interestingly, they are size–controllable by varying some parameters including concentration, reaction time, and mixing ratio. This review summarizes the design of DNA nanospheres and their extensive biomedical applications. First, the characteristics of DNA are briefly introduced, and different DNA nanostructures are mentioned. Then, the design of DNA nanospheres is emphasized and classified into three main categories, including Y–shaped DNA unit self-assembly by Watson–Crick base pairing, liquid crystallization and the dense packaging of ultra–long DNA strands generated via rolling circle amplification (RCA), and metal–DNA coordination–driven hybrids. Meanwhile, the advantages and disadvantages of different self–assembled DNA nanospheres are discussed, respectively. Next, the biomedical applications of DNA nanospheres are mainly focused on. Especially, DNA nanospheres serve as promising nanocarriers to deliver functional nucleic acids and drugs for biosensing, bioimaging, and therapeutics. Finally, the current challenges and perspectives for self-assembled DNA nanospheres in the future are provided.